Sphingosine‐1‐phosphate promotes tumor development and liver fibrosis in mouse model of congestive hepatopathy. Issue 1 (22nd December 2021) - Kawai, Hironari; Osawa, Yosuke; Matsuda, Michitaka; Tsunoda, Tomoyuki; Yanagida, Keisuke; Hishikawa, Daisuke; Okawara, Miku; Sakamoto, Yuzuru; Shimagaki, Tomonari; Tsutsui, Yuriko; Yoshida, Yuichi; Yoshikawa, Shiori; et al.
Abstract: Background and Aims: Chronic liver congestion reflecting right‐sided heart failure (RHF), Budd‐Chiari syndrome, or Fontan‐associated liver disease (FALD) is involved in liver fibrosis and HCC. However, molecular mechanisms of fibrosis and HCC in chronic liver congestion remain poorly understood. Approach and Results: Here, we first demonstrated that chronic liver congestion promoted HCC and metastatic liver tumor growth using murine model of chronic liver congestion by partial inferior vena cava ligation (pIVCL). As the initial step triggering HCC promotion and fibrosis, gut‐derived lipopolysaccharide (LPS) appeared to induce LSECs capillarization in mice and in vitro. LSEC capillarization was also confirmed in patients with FALD. Mitogenic factor, sphingosine‐1‐phosphate (S1P), was increased in congestive liver and expression of sphingosine kinase 1, a major synthetase of S1P, was increased in capillarized LSECs after pIVCL. Inhibition of S1P receptor (S1PR) 1 (Ex26) and S1PR2 (JTE013) mitigated HCC development and liver fibrosis, respectively. Antimicrobial treatment lowered portal blood LPS concentration, LSEC capillarization, and liver S1P concentration accompanied by reduction of HCC development and fibrosis in the congestive liver. Conclusions: In conclusion, chronic liver congestion promotes HCC development and liver fibrosis by S1P production from LPS‐induced capillarized LSECs. Careful treatment of both RHF and liver cancer might be necessary for patients with RHF with primary or metastatic liver cancer.